Co‐acquisition of mineral‐bound iron and phosphorus by natural Trichodesmium colonies - Shaked, Yeala; de Beer, Dirk; Wang, Siyuan; Zhang, Futing; Visser, Anna‐Neva; Eichner, Meri; Basu, Subhajit (Limnology and Oceanography, 2023)
Low iron (Fe) and phosphorus (P) ocean regions are often home to the globally important N2-fixing cyanobacterium Trichodesmium spp., which are physiologically adapted to Fe/P co-limitation. Given Trichodesmium's eminent ability to capture particles and the common associations between Fe and P in sediments and aerosols, we hypothesized that mineral bio-dissolution by Trichodesmium spp. may enable them to co-acquire Fe and P. We present a new sensitive assay to determine P uptake from particles, utilizing 33P-labeled ferrihydrite. To validate the method, we examined single natural Trichodesmium thiebautii colonies in a high-resolution radiotracer ß-imager, identifying strong colony-mineral interactions, efficient removal of external 33P-labeled ferrihydrite, and elevated 33P uptake in the colony core. Next, we determined bulk P uptake rates, comparing natural Red Sea colonies and P-limited Trichodesmium erythraeum cultures. Uptake rates by natural and cultured Trichodesmium were similar to P release rates from the mineral, suggesting tight coupling between dissolution and uptake. Finally, synthesizing P-ferrihydrite labeled with either 33P or 55Fe, we probed for Fe/P co-extraction by common microbial mineral solubilization pathways. Dissolution rates of ferrihydrite were accelerated by exogenous superoxide and strong Fe-chelator and subsequently enhanced 33P release and uptake by Trichodesmium. Our method and findings can facilitate further Fe/P co-acquisition studies and highlight the importance of biological mechanisms and microenvironments in controlling bioavailability and nutrient fluxes from particles.<br

Costs of Dust Collection by Trichodesmium: Effect on Buoyancy and Toxic Metal Release - Wang, Siyuan; Zhang, Futing; Koedooder, Coco; Qafoku, Odeta; Basu, Subhajit; Krisch, Stephan; Visser, Anna‐Neva; Eichner, Meri; Kessler, Nivi; Boiteau, Rene M.; Gledhill, Martha; Shaked, Yeala (Journal of Geophysical Research: Biogeosciences, 2024)
The marine cyanobacterium Trichodesmium has the remarkable ability to interact with and utilize air-borne dust as a nutrient source. However, dust may adversely affect Trichodesmium through buoyancy loss and exposure to toxic metals. Our study explored the effect of desert dust on buoyancy and mortality of natural Red Sea puff-shaped Trichodesmium thiebautii. Sinking velocities and ability of individual colonies to stay afloat with increasing dust loads were studied in sedimentation chambers. Low dust loads of up to ∼400 ng per colony did not impact initial sinking velocity and colonies remained afloat in the chamber. Above this threshold, sinking velocity increased linearly with the colony dust load at a slope matching prediction based on Stoke's law. The potential toxicity of dust was assessed with regards to metal dissolution kinetics, differentiating between rapidly released metals, which may impact surface blooms, and gradually released metals that may impact dust-centering colonies. Incubations with increasing dust concentrations revealed colony death, but the observed lethal dose far exceeded dust concentrations measured in coastal and open ocean systems. Removal of toxic particles as a mechanism to reduce toxicity was explored using SEM-EDX imaging of colonies incubated with Cu-minerals, yet observations did not support this pathway. Combining our current and former experiments, we suggest that in natural settings the nutritional benefits gained by Trichodesmium via dust collection outweigh the risks of buoyancy loss and toxicity. Our data and concepts feed into the growing recognition of the significance of dust for Trichodesmium's ecology and subsequently to ocean productivity.<br

Fate of nitrate during groundwater recharge in a fractured karst aquifer in Southwest Germany - Visser, Anna-Neva; Lehmann, Moritz F.; Rügner, Hermann; Mazo D'Affonseca, Fernando; Grathwohl, Peter; Blackwell, Nia; Kappler, Andreas; Osenbrück, Karsten (Hydrogeology Journal, 2021)
Over the past decades, fractured and karst groundwater systems have been studied intensively due to their high vulnerability to nitrate (NO3−) contamination, yet nitrogen (N) turnover processes within the recharge area are still poorly understood. This study investigated the role of the karstified recharge area in NO3− transfer and turnover by combining isotopic analysis of NO3− and nitrite (NO2−) with time series data of hydraulic heads and specific electrical conductivity from groundwater monitoring wells and a karstic spring in Germany. A large spatial variability of groundwater NO3− concentrations (0.1–0.8 mM) was observed, which cannot be explained solely by agricultural land use. Natural-abundance N and O isotope measurements of NO3− (δ15N and δ18O) confirm that NO3− derives mainly from manure or fertilizer applications. Fractional N elimination by denitrification is indicated by relatively high δ15N- and δ18O-NO3− values, elevated NO2− concentrations (0.05–0.14 mM), and δ15N-NO2− values that were systematically lower than the corresponding values of δ15N-NO3−. Hydraulic and chemical response patterns of groundwater wells suggest that rain events result in the displacement of water from transient storage compartments such as the epikarst or the fissure network of the phreatic zone. Although O2 levels of the investigated groundwaters were close to saturation, local denitrification might be promoted in microoxic or anoxic niches formed in the ferrous iron-bearing carbonate rock formations. The results revealed that (temporarily) saturated fissure networks in the phreatic zone and the epikarst may play an important role in N turnover during the recharge of fractured aquifer

Impact of reactive surfaces on the abiotic reaction between nitrite and ferrous iron and associated nitrogen and oxygen isotope dynamics - Visser, Anna-Neva; Wankel, Scott D.; Niklaus, Pascal A.; Byrne, James M.; Kappler, Andreas; Lehmann, Moritz F. (Biogeosciences, 2020)
Anaerobic nitrate-dependent Fe(II) oxidation (NDFeO) is widespread in various aquatic environments and plays a major role in iron and nitrogen redox dynamics. However, evidence for truly enzymatic, autotrophic NDFeO remains limited, with alternative explanations involving the coupling of heterotrophic denitrification with the abiotic oxidation of structurally bound or aqueous Fe(II) by reactive intermediate nitrogen (N) species (chemodenitrification). The extent to which chemodenitrification is caused (or enhanced) by ex vivo surface catalytic effects has not been directly tested to date. To determine whether the presence of either an Fe(II)-bearing mineral or dead biomass (DB) catalyses chemodenitrification, two different sets of anoxic batch experiments were conducted: 2 mM Fe(II) was added to a low-phosphate medium, resulting in the precipitation of vivianite (Fe3(PO4)2), to which 2 mM nitrite () was later added, with or without an autoclaved cell suspension ( cells mL−1) of Shewanella oneidensis MR-1. Concentrations of nitrite (), nitrous oxide (N2O), and iron (Fe2+, Fetot) were monitored over time in both set-ups to assess the impact of Fe(II) minerals and/or DB as catalysts of chemodenitrification. In addition, the natural-abundance isotope ratios of and N2O (δ15N and δ18O) were analysed to constrain the associated isotope effects. Up to 90 % of the Fe(II) was oxidized in the presence of DB, whereas only ∼65 % of the Fe(II) was oxidized under mineral-only conditions, suggesting an overall lower reactivity of the mineral-only set-up. Similarly, the average reduction rate in the mineral-only experiments (0.004±0.003 mmol L−1 d−1) was much lower than in the experiments with both mineral and DB (0.053±0.013 mmol L−1 d−1), as was N2O production (204.02±60.29 nmol L−1 d−1). The N2O yield per mole reduced was higher in the mineral-only set-ups (4 %) than in the experiments with DB (1 %), suggesting the catalysis-dependent differential formation of NO. N- isotope ratio measurements indicated a clear difference between both experimental conditions: in contrast to the marked 15N isotope enrichment during active reduction ( ‰) observed in the presence of DB, loss in the mineral-only experiments exhibited only a small N isotope effect (<+1 ‰). The -O isotope effect was very low in both set-ups ( <1 ‰), which was most likely due to substantial O isotope exchange with ambient water. Moreover, under low-turnover conditions (i.e. in the mineral-only experiments as well as initially in experiments with DB), the observed isotope systematics suggest, transiently, a small inverse isotope effect (i.e. decreasing δ15N and δ18O with decreasing concentrations), which was possibly related to transitory surface complexation mechanisms. Site preference (SP) of the 15N isotopes in the linear N2O molecule for both set-ups ranged between 0 ‰ and 14 ‰, which was notably lower than the values previously reported for chemodenitrification. Our results imply that chemodenitrification is dependent on the available reactive surfaces and that the (rather than the N2O) isotope signatures may be useful for distinguishing between chemodenitrification catalysed by minerals, chemodenitrification catalysed by dead microbial biomass, and possibly true enzymatic NDFeO.<br

In situ incubation of iron(II)-bearing minerals and Fe(0) reveals insights into metabolic flexibility of chemolithotrophic bacteria in a nitrate polluted karst aquifer - Visser, Anna-Neva; Martin, Joseph D.; Osenbrück, Karsten; Rügner, Hermann; Grathwohl, Peter; Kappler, Andreas (Science of the Total Environment, 2024)
Groundwater nitrate pollution is a major reason for deteriorating water quality and threatens human and animal health. Yet, mitigating groundwater contamination naturally is often complicated since most aquifers are limited in bioavailable carbon. Since metabolically flexible microbes might have advantages for survival, this study presents a detailed description and first results on our modification of the BacTrap© method, aiming to determine the prevailing microbial community's potential to utilize chemolithotrophic pathways. Our microbial trapping devices (MTDs) were amended with four different iron sources and incubated in seven groundwater monitoring wells for ∼3 months to promote growth of nitrate-reducing Fe(II)-oxidizing bacteria (NRFeOxB) in a nitrate-contaminated karst aquifer. Phylogenetic analysis based on 16S rRNA gene sequences implies that the identity of the iron source influenced the microbial community's composition. In addition, high throughput amplicon sequencing revealed increased relative 16S rRNA gene abundances of OTUs affiliated to genera such as Thiobacillus, Rhodobacter, Pseudomonas, Albidiferax, and Sideroxydans. MTD-derived enrichments set up with Fe(II)/nitrate/acetate to isolate potential NRFeOxB, were dominated by e.g., Acidovorax spp., Paracoccus spp. and Propionivibrio spp. MTDs are a cost-effective approach for investigating microorganisms in groundwater and our data not only solidifies the MTD's capacity to provide insights into the metabolic flexibility of the aquifer's microbial community, but also substantiates its metabolic potential for anaerobic Fe(II) oxidation.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Chemolithotrophic growth; Corrosion; Karst groundwater; Nitrate; Nitrate-reducing Fe(II) oxidation

Unchanged nitrate and nitrite isotope fractionation during heterotrophic and Fe(II)-mixotrophic denitrification suggest a non-enzymatic link between denitrification and Fe(II) oxidation - Visser, Anna-Neva; Wankel, Scott D.; Frey, Claudia; Kappler, Andreas; Lehmann, Moritz F. (Frontiers in Microbiology, 2022)
Natural-abundance measurements of nitrate and nitrite (NOx) isotope ratios (δ15N and δ18O) can be a valuable tool to study the biogeochemical fate of NOx species in the environment. A prerequisite for using NOx isotopes in this regard is an understanding of the mechanistic details of isotope fractionation (15ε, 18ε) associated with the biotic and abiotic NOx transformation processes involved (e.g., denitrification). However, possible impacts on isotope fractionation resulting from changing growth conditions during denitrification, different carbon substrates, or simply the presence of compounds that may be involved in NOx reduction as co-substrates [e.g., Fe(II)] remain uncertain. Here we investigated whether the type of organic substrate, i.e., short-chained organic acids, and the presence/absence of Fe(II) (mixotrophic vs. heterotrophic growth conditions) affect N and O isotope fractionation dynamics during nitrate (NO3–) and nitrite (NO2–) reduction in laboratory experiments with three strains of putative nitrate-dependent Fe(II)-oxidizing bacteria and one canonical denitrifier. Our results revealed that 15ε and 18ε values obtained for heterotrophic (15ε-NO3–: 17.6 ± 2.8‰, 18ε-NO3–:18.1 ± 2.5‰; 15ε-NO2–: 14.4 ± 3.2‰) vs. mixotrophic (15ε-NO3–: 20.2 ± 1.4‰, 18ε-NO3–: 19.5 ± 1.5‰; 15ε-NO2–: 16.1 ± 1.4‰) growth conditions are very similar and fall within the range previously reported for classical heterotrophic denitrification. Moreover, availability of different short-chain organic acids (succinate vs. acetate), while slightly affecting the NOx reduction dynamics, did not produce distinct differences in N and O isotope effects. N isotope fractionation in abiotic controls, although exhibiting fluctuating results, even expressed transient inverse isotope dynamics (15ε-NO2–: –12.4 ± 1.3 ‰). These findings imply that neither the mechanisms ordaining cellular uptake of short-chain organic acids nor the presence of Fe(II) seem to systematically impact the overall N and O isotope effect during NOx reduction. The similar isotope effects detected during mixotrophic and heterotrophic NOx reduction, as well as the results obtained from the abiotic controls, may not only imply that the enzymatic control of NOx reduction in putative NDFeOx bacteria is decoupled from Fe(II) oxidation, but also that Fe(II) oxidation is indirectly driven by biologically (i.e., via organic compounds) or abiotically (catalysis via reactive surfaces) mediated processes co-occurring during heterotrophic denitrification.<br